Simulation of electromechanical interactions of permanent-magnet direct-drive wind turbines using the fast aeroelastic simulator. - White, Warren N.; Miller, Ruth D.; Ochs, David S. (My University, 2013)
Two detailed models of permanent-magnet direct-drive (PMDD) wind turbines with full converters are presented in this paper: one for a 10-kW turbine, and one for a 5-MW turbine. The models are verified by comparing the power curves found through simulation with field test data. Other results are also presented that show the unprecedented detail of the models. The mathematical representations include switching models for the full converters, circuit models for permanent-magnet synchronous generators, realistic aerodynamics, tower and blade vibrations, and many other variables. The models are valuable tools for wind turbine design and research and can be used for a wide range of purposes including control system design, sensitivity analysis, and interactions between the electrical and mechanical parts of a PMDD wind turbine. Simulation of the models is carried out in the MATLAB/Simulink environment using the FAST aeroelastic simulator.
Keywords: FAST; Permanent-magnet synchronous generator (PMSG); Pulsewidth modulated (PWM) converters; Wind energy